2019
DOI: 10.4067/s0719-81322019000200067
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ginger on testis of Broiler breeders

Abstract: The rhizome of ginger is a fresh or dried organ of the plant Zingiber officinale, which has been used as a medicine since ancient times. The present study was conducted to examine the effects of ginger on testicular histomorphometry in roosters of broiler chicken flocks. Eighty single-day rooster of broiler chickens belonging to 308 Ross breed was used in the present study. The chickens were divided into two groups with 40 broiler roosters (experimental and control groups). Initially, the rhizome of ginger was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As argued by Hamzehnezhad et al (2019) the increase in spermatozoid number is due to the increase in spermatogenesis process, which the concentration of testosterone can influence the process. They concluded that the increase in spermatogenesis process may due to the stimulating effect of increased testosterone hormone in roosters which fed ginger supplemented diet.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As argued by Hamzehnezhad et al (2019) the increase in spermatozoid number is due to the increase in spermatogenesis process, which the concentration of testosterone can influence the process. They concluded that the increase in spermatogenesis process may due to the stimulating effect of increased testosterone hormone in roosters which fed ginger supplemented diet.…”
Section: Discussionmentioning
confidence: 87%
“…As argued by Hamzehnezhad et al (2019) the increase in spermatozoid number is due to the increase in spermatogenesis process, which the concentration of testosterone can influence the sperm un-saturated and saturated fatty acid content, respectively;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F ertility is considered an essential part of poultry industry and a lot of money are paid annually to improve the fertility parameters (Hamzehnezhad et al, 2019). Cocks play a vital role in flock fertility because in poultry breeding the ratio of male to female is low (Ommati et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cocks play a vital role in flock fertility because in poultry breeding the ratio of male to female is low (Ommati et al, 2013). Therefore, promoting fertility indices in cocks is crucial to achieve the highest productivity (Hamzehnezhad et al, 2019). Fluconazole (FCZ) is a triazole antifungal agent which can be administered both orally and intravenously.…”
Section: Introductionmentioning
confidence: 99%